Dinamika Perilaku Menyimpang: Analisis Narkoba sebagai Pelarian Dari Masalah, Studi Kasus Lapas Cibinong dan Lapas Cipinang - Hisyam, Ciek Julyanti; Aprilina, Ajeng Ayundha; Putri, Almaida Handara; Putri, Calista Olivia Adeline; Syabella, Izmi; Delima, Kiranti Bening Penta; Permana, Muhammad Akbar Putra; Faresh, Muhammad Haichal; Rachmawati, Vania (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Drug abuse in Indonesia is a form of social deviance influenced by psychological pressure, structural conditions, and weak social ties. This phenomenon is not only related to legal aspects but also arises as a response to stress, anxiety, and negative emotional experiences. Theories such as self-medication, escapism, Durkheim and Merton's Anomie, and Agnew's General Strain Theory suggest that drug abuse behavior can develop due to imbalanced norms, social tension, and an individual's inability to cope with life's pressures. In inmates, these factors are exacerbated by challenging social and economic experiences prior to their incarceration, increasing the risk of involvement in drug use and trafficking. This study emphasizes the need for a multidimensional approach to understanding this deviance and supporting rehabilitation and social reintegration efforts. Strengthening the roles of families, communities, and educational institutions in preventing drug abuse is crucial for providing ongoing support. A deeper understanding of the patterns of individual involvement in drug abuse is key to designing more effective prevention programs, based on psychological, social, and structural approaches to reduce the long-term impact of drug abuse on society.